2018
DOI: 10.1080/22423982.2017.1422670
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led diabetic retinopathy screening: a pilot study to evaluate a new approach to vision care for Canadian Aboriginal peoples

Abstract: Diabetic retinopathy is the most common cause of new cases of blindness and is pandemic among Aboriginal people around the world. To reduce health inequities, accessible vision screening among these high-risk populations is essential. To assess cardio-metabolic co-morbidities associated with type 2 diabetes and the use of a portable fundus camera as a novel approach for convenient, earlier and more accessible vision screening for Aboriginal peoples living with type 2 diabetes in northern and remote Canadian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…while there is no significant relationship was founded between knowledge with gender or duration of DM. This result agrees with Qi et al [62] who illustrated that age was the main factor significantly associated with knowledge scores. Also this in the same line with Neama et al [63] who revealed that most patients reported have poor level of knowledge related to DR.…”
Section: Discussionsupporting
confidence: 93%
“…while there is no significant relationship was founded between knowledge with gender or duration of DM. This result agrees with Qi et al [62] who illustrated that age was the main factor significantly associated with knowledge scores. Also this in the same line with Neama et al [63] who revealed that most patients reported have poor level of knowledge related to DR.…”
Section: Discussionsupporting
confidence: 93%
“…The crucial role of nurses/technicians in DR screening with the aim of reducing the prevalence of blindness due to diabetes and reducing diabetes-related costs has been confirmed and reported earlier in numerous scientific articles and reviews [33][34][35][36]. In many diabetes centers in Europe and worldwide, educated nurses/technicians especially, in addition to fundus photographing, grade the fundus images and refer each patient with suspicious and positive results to ophthalmologists for further diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 96%
“…More than achieving universal health coverage in a country, equity should be prioritized, otherwise, socially advantaged groups will be more likely to use the new or improved services [71,72]. Specific actions include the following: (1) access: increasing the number of clinic sites, rural locations, and eye care sessions, not only with ophthalmologists, but also with other eye health practitioners as optometrists, ophthalmic technologists, and/or trained nurses should improve the number of patient seen, dispensing spectacles, and surgery referrals [72,73]; (2) integration with family medicine/primary care: several communities have general health programs with systemic condition screening and could include ocular health screening tools into their practice to detect and timely refer cases of vision impairment and blindness for specialized care [19,72,74]; (3) telemedicine: several telemedicine protocols in ophthalmology focused on diabetes retinopathy, glaucoma, and cataract have been shown to be effective in populations living in remote areas and should be used as models towards Indigenous population groups [75][76][77]; (4) customized propaedeutics: specific techniques should be indicated to populations living in remote areas, for example, manual small incision cataract surgery (MSICS) techniques in resource-constrained health care settings such as Indigenous communities [78]; (5) education on eye health: by promoting basic knowledge on eye health, the population can better understand the importance of seeking timely treatment, improving visual outcomes [79,80]; (6) quality data: more studies focused on Indigenous population's eye health should be performed with appropriate methodology and collection of key indicators such as eCSC and eREC, and studies performed in the general population should collect data on the participants' ethnicity/race [52,53].…”
Section: Discussionmentioning
confidence: 99%